2015
DOI: 10.1097/hp.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Dose Rates Near a Radioactive Patient Evaluated Using Various Source Models

Abstract: This study investigated radiation exposures from nuclear medicine patients by systematically comparing the dose rates calculated using various source models, ranging from simplified point, line, and cylinder sources to high-quality anthropomorphic phantoms. Three widely used radionuclides, (99m)Tc, (18)F, and I(131), were considered in these source models with uniform or organ-dependent distributions. Conducting Monte Carlo simulations with anthropomorphic phantoms is a realistic but time-consuming approach. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The biokinetic parameters describing the whole-body retention (Liu et al 2014) are also of importance and should be chosen with care. In Liu et al (2015b), mathematical phantoms and a static activity distribution have been used to calculate dose rate at 30 and 100 cm by Monte Carlo simulations. It was concluded that the line source model is a good approximation for 99m Tc, 18 F, and 131 I used for remnant ablations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The biokinetic parameters describing the whole-body retention (Liu et al 2014) are also of importance and should be chosen with care. In Liu et al (2015b), mathematical phantoms and a static activity distribution have been used to calculate dose rate at 30 and 100 cm by Monte Carlo simulations. It was concluded that the line source model is a good approximation for 99m Tc, 18 F, and 131 I used for remnant ablations.…”
Section: Discussionmentioning
confidence: 99%
“…It should be acknowledged that despite this, the approach is usually accepted (Matheoud et al 2004; De Carvalho et al 2011; D'Alessio et al 2015; Liu et al 2015b). The experimental evidences for such an approach are limited to a few studies (Willegaignon et al 2007; Yi et al 2013; D'Alessio et al 2015) and limited to a small number of short distances or a single distance (Liu 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations